Improvement Skills Husband- Wife Communication through Guidance Family to the PKK Mothers of RT.1/RW.1 Kenteng Village - Syarifah, Dian Farah; Herawan, Sunu; Belva, Edgina; Hilmi, Asa Faradiba; Fibrianti, Nurul (Universitas Negeri Semarang, 2025)
Good communication between husband and wife is an important factor in maintaining household harmony. However, there are still many couples who experience difficulties in communicating so that misunderstandings often occur that can cause conflicts. This family guidance program is designed to assist PKK RT 1/RW 1 Kenteng Village women in improving their communication skills with their partners. This activity is designed in the form of interactive materials that contain effective communication techniques, such as listening attentively, controlling emotions, and expressing opinions properly and correctly. The results of the evaluation showed that there was an increase in participants' understanding in communicating with their partners. The results of the evaluation showed an increase in participants' understanding of communicating with their partners. Based on pretest and post-test data from 11 participants, there was an increase in the average score of effective communication comprehension from 38.36 in the pretest to 52.55 in the post-test. This shows an average increase of 14.18 points, or equivalent to a percentage increase of 35.68%. This program helps participants in reducing misunderstandings, increasing openness in communication, and creating more harmonious domestic relationships.